Sociological Implications of Social Exchange in Regional Head Elections in Gorontalo Province - Apris Ara Tilome (Borong Newinera Publisher, 2022)
This study aims to dissect the Sociological Implications of Social Exchange Post-Election of Regional Head Candidates in Gorontalo Province. Methods of data collection using interviews, documentation and retrospective. This study produced several findings, including: First; Political elite social exchange relations are strategic situations that are mutually dependent, need each other, and are mutually beneficial as well as an effort to consolidate power to achieve electability/victory in the momentum of regional head elections. Second; The pattern of social exchange is based on a number of ownership potentials in the form of elite, figure and financial resources, which can determine the social forces that are considered by political parties to give party approval/recommendations to pairs of candidates for regional heads. Third, the social exchange strategy between party elites and political elites uses each other to achieve victory in the contestation of regional head elections. This study concludes that the sociological implications of social interactions take place in people's lives before and after the election of regional head candidates. There are divisions in society due to friction generated in the election of regional heads originating from social exchange relations, patterns of social exchange and social exchange strategies both individually and in groups of political elites and party elites.